Caracterización de la calidad del agua para consumo humano en sectores rurales del cantón Quevedo - López Rodríguez, Medardo Rolando (2019)
In this work, the quality of the groundwater of the deep wells for human consumption located in the San Carlos and La Esperanza parishes, belonging to the Quevedo canton, was characterized. The population refers to difficult access and that the water is of poor quality. The vulnerability analysis reports that the water from the wells of the San Carlos parish maintains a moderate vulnerability and the wells of the La Esperanza parish a high vulnerability. The water quality analyzes indicate that the values reported in 2014 are lower than those obtained in 2019 and a higher presence of manganese in the four wells studied. Some guidelines of the socio-environmental plan and the pertinent strategies that must be promoted to reduce the contamination levels of deep well water are proposed. Keywords: mitigate, permissible limits, hydromorphological, anthropogenic.